POPULATION DISTRIBUTION OF WILD CROCODILE (Crocodylus porosus) IN PENINSULAR MALAYSIA - KHAIRUL AMIRIN, MOHAMED; Muhammad Hafiizuddin, Shaari; Muhammad Dahlan, Othman; Fazlullah, Omar Ahmad; Azmatun, Abd Jamin; Shahrul Nizam, Mahat; Mohd Syafiq, Ab Rahman; Zulkifli, Mohd Noor; Ismail, Hj Mamat; Jeffrine Rovie, Ryan Japning; DAVID, MAGINTAN (Department of Wildlife and National Parks (PERHILITAN), Peninsular Malaysia., 2025)
Estuarine crocodiles (Crocodylus porosus) are widely distributed in Peninsular Malaysia. As a highly valuable species, they are highly exploited and traded in the international market for their skin, meat and other derivatives. To protect and regulate the sustainable trade of the species, Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) requires countries to conduct non-detrimental findings (NDF) before any permit for trade can be issued. Sarawak separately have managed to downgrade the species to Appendix II from Appendix I based on a long-term survey and data which allows for regulated trade. In Peninsular Malaysia however, no holistic population distribution survey was conducted to estimate their numbers in the wild. Therefore, to permit legal and sustainable exploitation for international trade, the management authority, Department of Wildlife and National Parks (DWNP) officially started a crocodile NDF survey in 2016 to determine the distribution of the species. Using human-wildlife conflicts data and interviews as a baseline for survey locations, a spotlight survey was used to record the presence of C. porosus and size estimation were done. In total, 28 tributaries were surveyed where 19 locations were identified as the habitat of C. porosus. Approximately 1,076.05 kilometres of travelling distance was surveyed with a mean occurrence of 0.454 individual per kilometres recorded. A total of 215 individuals were sighted and verified with the size estimation range of less than 1-metres to 5-metres. There is a need to conduct a bigger scale inventory and survey focusing on these tributaries to holistically map the crocodile habitat including its prey for wildlife management plan.